Constitución y control de constitucionalidad: hacia una reconfiguración democrática-deliberativa desde Atria, Habermas y Landemore - Inarra Zeballos, Luis Gonzalo (2025)
This article critically examines constitutional courts in Latin America and raises the need to rethink the control of constitutionality from a deliberative perspective. Following Fernando Atria's criticisms and reflections on issues such as neoconstitutionalism, constitutional jurisdiction and constitutional concepts, as well as his conception of democratic deliberation and that of Jürgen Habermas, it integrates Hélène Landemore's proposal on open and lottocratic democracy as a way to democratize the control of constitutionality, with a view to laying the foundations for an institutional redesign that overcomes the limitations of the current judicial model and revitalizes the democratic principle.